Neuropsychiatric complications in a patient with Marfan syndrome. Issue 4 (27th February 2013) - Lee, Chin-Pang; Chu, Chun-Lin; Liu, Chia-Yih; Chen, Chia-Hsiang
Abstract : Background: Marfan syndrome (MFS) is an autosomal dominant disorder of fibrillin-1 gene mutations, with the involvement of cardiovascular, skeletal, and ocular systems. In addition to physical abnormalities, MFS patients are also found to be susceptible to schizophrenia and other psychiatric conditions. Objectives: Awareness of the association between MFS and psychiatric conditions would improve the clinical management of MFS patients to reduce the risk or even to prevent the development of psychiatric complications in MFS patients. Methods: Here, we describe a male MFS patient who manifested incoherent speech and impaired cognitive and social function at the age of 40 years. Results and conclusion: His mental dysfunction could be attributed to his bilateral cerebral infarction, which is a neurovascular complication associated with MFS.